2016
DOI: 10.1002/rra.3003
|View full text |Cite
|
Sign up to set email alerts
|

Age‐0 Shovelnose Sturgeon Prey Consumption in the Lower Missouri River

Abstract: A lack of nutritious food during the first year of life is a hypothesized factor that may limit survival of endangered pallid sturgeon Scaphirhynchus albus in the lower Missouri River (LMOR). Unfortunately, information for age-0 pallid sturgeon diets remains limited, but diet analyses for age-0 Scaphirhynchus spp. (sturgeon hereafter) have occurred. Little information, however, exists on age-0 sturgeon diets in the LMOR; thus, our primary objective was to document age-0 sturgeon diets in this system. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…The current hypothesis is that slow velocity areas (<0.08 m/s) produce chironomids, and river currents transport these prey items to age‐0 Scaphirhynchus sturgeon foraging areas (Jacobson et al, ). Age‐0 Scaphirhynchus sturgeon in the LMOR mainly consume chironomids (Civiello et al, ; Gosch et al, ; Gosch et al, ), but the origin of these prey items (i.e., transported in the drift, produced in the benthos of foraging areas, or a combination of the two) is currently unknown. Additional research regarding the origin of chironomid prey available to Scaphirhynchus sturgeon would help identify and refine estimates of these essential habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current hypothesis is that slow velocity areas (<0.08 m/s) produce chironomids, and river currents transport these prey items to age‐0 Scaphirhynchus sturgeon foraging areas (Jacobson et al, ). Age‐0 Scaphirhynchus sturgeon in the LMOR mainly consume chironomids (Civiello et al, ; Gosch et al, ; Gosch et al, ), but the origin of these prey items (i.e., transported in the drift, produced in the benthos of foraging areas, or a combination of the two) is currently unknown. Additional research regarding the origin of chironomid prey available to Scaphirhynchus sturgeon would help identify and refine estimates of these essential habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also evaluated diet composition of age‐0 Scaphirhynchus sturgeon (Braaten, Fuller, & McClenning, ; Civiello et al, ; Gosch et al, ; Harrison, Slack, & Killgore, ; Sechler et al, ; Sechler, Phelps, Tripp, & Garvey, ), and Gosch, Civiello, Gemeinhardt, Bonneau, and Long () found that age‐0 pallid and shovelnose sturgeon ( Scaphirhynchus platyrhynchus ) consumed similar prey items; however, relationships between prey consumption and habitat, such as depth and velocity, were not investigated. Furthermore, past research has focused on the depths and velocities at, or very near, the point of capture rather than quantifying habitats available to age‐0 Scaphirhynchus sturgeon at a variety of spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Wildlife Service 1990), and researchers have recently developed a suite of hypotheses highlighting potential factors that may be limiting pallid sturgeon recruitment to age-1 (Jacobson et al 2016). Inadequate food availability during early life history is one of the hypotheses garnering recent attention (Gosch et al 2016, 2018, Gemeinhardt et al 2019 and is currently the focus of habitat restoration efforts on the lower Missouri River (LMOR; Gavins Point Dam, South Dakota, downstream to the Mississippi River confluence at St. Louis, Missouri). Additionally, some of the habitat restoration targets were based on age-0 Scaphirhynchus sturgeon capture data due to the scarcity of pallid sturgeon (Gemeinhardt et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This prey specificity is similar to that of age‐0 shovelnose sturgeon and young‐of‐the‐year white sturgeon. Age 0 shovelnose sturgeon, ranging from 15 to 53 mm, prey almost exclusively on chironomid larvae (>98%) in the lower Missouri River (Gosch et al, ), while young‐of‐the‐year white sturgeon in the Lower Columbia River primarily feed on gammarid amphipods year‐round (Muir et al, ). Considering the diversity of prey in rivers, prey preference, sampling time, abundance of benthic invertebrates, and, to some extent, palatability may account for prey selection.…”
Section: Discussionmentioning
confidence: 99%